Quantitative expansion microscopy for the characterization of the spectrin periodic skeleton of axons using fluorescence microscopy - Martínez, Gaby F. (Sci Rep, 2020)
Fluorescent nanoscopy approaches have been used to characterize the periodic organization of actin, spectrin and associated proteins in neuronal axons and dendrites. This membrane-associated periodic skeleton (MPS) is conserved across animals, suggesting it is a fundamental component of neuronal extensions. The nanoscale architecture of the arrangement (190 nm) is below the resolution limit of conventional fluorescent microscopy. Fluorescent nanoscopy, on the other hand, requires costly equipment and special analysis routines, which remain inaccessible to most research groups. This report aims to resolve this issue by using protein-retention expansion microscopy (pro-ExM) to reveal the MPS of axons. ExM uses reagents and equipment that are readily accessible in most neurobiology laboratories. We first explore means to accurately estimate the expansion factors of protein structures within cells. We then describe the protocol that produces an expanded specimen that can be examined with any fluorescent microscopy allowing quantitative nanoscale characterization of the MPS. We validate ExM results by direct comparison to stimulated emission depletion (STED) nanoscopy. We conclude that ExM facilitates three-dimensional, multicolor and quantitative characterization of the MPS using accessible reagents and conventional fluorescent microscopes.